Teratogenic effects of Metoprolol in the chick embryos - Abed, Abbas Razzaq (The Iraqi Journal of Veterinary Medicine, 2015)
This study was conducted to demonstrate the effect of Metoprolol on chicken embryos during the period of cuddling automated .This study was completed in Babylon hatchery dedicated to the production of chick chickens, which is located in the province of Babylon. One hundred eggs (Belgian origin, CZ 1924) were divided into equal four groups. The first group injected eggs by Metaprolol at dose 10 mg /70kg BW, and the second group eggs was injected by Metoprolol at dose 15 mg /70kg BW, while eggs in the third group was injected by physiological normal saline only and the fourth group did not inject their eggs any material and considered the control group and all the eggs used in this experiment to take on the fourth day of cuddling. The results of this study showed a decrease in the percentage hatching in groups injected with Metoprolol (T1 and T2 groups, 4% and 13%, respectively) compared to the T3 and the control groups. Also showed the results of the current study, no significant difference at the level of (P <0.05) in the weights of embryos after hatching. While histopathological examination showed the presence of pathological lesions in the heart tissue in injected eggs groups by Metoprolol (T1 and T2 groups) and included these changes infiltration of inflammatory cells, thickening in epicardium and the presence of vacuolation in heart tissue with the appearance of edema, heart tissue damage, congestion in the blood vessels and the occurrence of hemorrhage.